2017
DOI: 10.1111/plb.12652
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology of the carnivorous plant Pinguicula moranensis (Lentibulariaceae)

Abstract: The interaction of plants with pollinators can be a determinant of their reproductive fitness. However, information about the pollination biology of carnivorous plants is scarce. To increase knowledge of reproductive ecology of carnivorous plants we focused on Pinguicula moranensis. Specifically, based on the presence of large, zygomorphic and spurred flowers, we predicted higher reproductive fitness in cross-pollinated than in self-pollinated flowers. Within a plot of 51 m we characterised the reproductive ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
1
17
0
4
Order By: Relevance
“…Most Lentibulariaceae species (genera Pinguicula, Genlisea and Utricularia) are pollinated by insects (Taylor, 1989;Zamora, 1999;Hobbhahn et al, 2006;Fleischmann, 2012;Clivati et al, 2014;Villegas and Alcalá, 2018;Aranguren et al, 2018;Cross et al, 2018;Płachno et al, 2018a). Bird pollination is rare and has probably evolved independently three times in this family; once in Pinguicula (two species from the same section) and twice in Utricularia (three species, two non-related sections).…”
Section: Introductionmentioning
confidence: 99%
“…Most Lentibulariaceae species (genera Pinguicula, Genlisea and Utricularia) are pollinated by insects (Taylor, 1989;Zamora, 1999;Hobbhahn et al, 2006;Fleischmann, 2012;Clivati et al, 2014;Villegas and Alcalá, 2018;Aranguren et al, 2018;Cross et al, 2018;Płachno et al, 2018a). Bird pollination is rare and has probably evolved independently three times in this family; once in Pinguicula (two species from the same section) and twice in Utricularia (three species, two non-related sections).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fitness of carnivorous species could depend on interactions with both prey and pollinators (Jürgens, Sciligo, Witt, El-Sayed, & Suckling, 2012). Carnivorous plants display wide diversity of reproductive systems, and studies addressing reproductive ecology have documented variation in flower structure and histochemistry, flower phenology and longevity, mating system, pollination syndrome, and visitation rate, among others (Adam, 1998;Chua, 2000;Clivati, Cordeiro, Płachno, & Miranda, 2014;Hobbhahn, Küchmeister, & Porembski, 2006;Kato, 1993;Lowrie, 2001;Meindl & Mesler, 2011;Molano-Flores et al, 2018;Molau, 1993;Murza & Davis, 2003;Ne´eman et al, 2006;Olivencia, Claver, & Alcaraz, 1995;Płachno et al, 2018;Renner, 1989;Schnell, 1983;Villegas & Alcalá, 2017). These studies have identified selfing and outbreeding species, but the information on the effects of varying distance to pollen donors is scarce in carnivorous plant species.…”
mentioning
confidence: 99%
“…This information is needed to improve our understanding of the fitness consequences of outbreeding species when exposed to inbreeding. This scenario is likely to occur as a result of the spatial distribution of individual plants and the foraging pattern of pollinators, despite traits promoting outcrossing (Clivati et al, 2014;Hobbhahn et al, 2006;Molano-Flores et al, 2018;Villegas & Alcalá, 2017).…”
mentioning
confidence: 99%
“…They are grouped into one clade-Mexican-Central American-Caribbean Clade I (Cieslak et al 2005). From examined species, pollinators (butterflies) were recorded only for P. moranensis (Villegas and Alcalá 2018); however, flower structure (coloured flowers with long and thin spurs) suggests that also other examined species are pollinated by butterflies.…”
Section: Discussionmentioning
confidence: 98%
“…The Mexican Pinguicula species (P. moranensis), which produce large, coloured, hercogamous flowers that have long spurs, are pollinated by Lepidoptera (Zamudio 2001;Villegas and Alcalá 2018, see Fig. 5 in Villegas and Alcalá 2018, which presents a beautiful "Schematic representation of pollination in Pinguicula moranensis"). According to Abrahamczyk et al (2017), Pinguicula macrophylla and P. moctezumaeare are also pollinated by Lepidoptera.…”
Section: Introductionmentioning
confidence: 99%